Envelhecimento populacional: uma realidade brasileira The ageing of population: the Brazilian scene - Luiz Roberto Ramos; Renato P. Veras; Alexandre Kalache (Universidade de São Paulo, 1987)
São apresentados dados mostrando que tanto as taxas de mortalidade quanto as de fecundidade estão decaindo significativamente para a população brasileira, como um todo, desde 1940 e 1960, respectivamente. Pirâmides etárias por sexo são analisadas à luz das mudanças demográficas. Enfatiza-se o fato de que, desde 1940, é o grupo etário com 60 anos ou mais o que proporcionalmente mais cresce na população brasileira. De 1980 ao ano 2000 eles crescerão 107%, enquanto os menores de 15 anos crescerão apenas 14%. Comparando-se as taxas de crescimento dos idosos no Brasil e na Inglaterra, a tendência é haver um crescimento cada vez menor na Inglaterra (230% entre 1900-1960 e 80% entre 1960-2025) e um crescimento cada vez maior no Brasil (497% e 917% respectivamente). Os dados mostram que a expectativa de vida ao nascimento no Estado de São Paulo passou de 57 anos, em 1950, para 70 anos, em 1982. Já em 1982, uma mulher no Município de São Paulo podia aos 45 anos esperar viver mais do que uma mulher da mesma idade na Inglaterra. Em termos de sobrevida, 77% da coorte de mulheres nascidas no Município de São Paulo, em 1982 deverão estar vivas aos 65 anos, comparado com 85% na Inglaterra. Para os homens os dados são de 62% e 75%, respectivamente. Conclui-se que o Brasil, embora ainda longe de resolver os problemas relacionados à infância, já está tendo que enfrentar as implicações sociais e de saúde decorrentes de um processo de envelhecimento comparável àquele experimentado pelos países mais desenvolvidos. It was focuse on the ageing process in Brazil, giving evidence of the boom of elderly people in the country, bearing in mind that by the year 2025 they will represent the 6th largest elderly population in the world. Data are presented showing that both Infant Mortality Rates and Fertility Rates have been decreasing significantly for the whole population since 1940 and 1960 respectively. Age-sex pyramids are analysed in the light of the demographic changes. It is stressed that the elderly have been the fastest growing age-group in Brazil since 1940. In fact, from 1980 up to the year 2000, the over-60s will increase 107% whereas the under 15s will increase only 14%. Comparing the rates of growth for the elderly populations in England and Brazil, the tendency is to have a decreasing rate of growth in England (230% between 1900-1960 and 80% between 1960-2025) and an increasing rate of growth in Brazil (497% and 917% respectively). Life tables are presented from 1950 to 1982 for the population of S. Paulo (a highly industrialised urban area). Life Expectancy, Survival, and Mortality Rate curves are generated from these life tables. The data show that the expectation of life at birth in S. Paulo State (Brazil) has risen from 57 years in the 50's, to 70 years in 1982. Interestingly enough, in that year, a woman in the county of S. Paulo, after the age of 45, could already expect to live more than women of the same age in England. In terms of survival chances, 77% of the cohort of women born in the county of S. Paulo in 1982 are expected to be alive at the age of 65, compared to 85% in England. Figures for men are 62% and 75% respectively. It was concluded that although far from solving the problems related to the very young, the Brazilian authorities are already facing an ageing process comparable to that experienced by the developed countries, with all its implications for the health and social care systems.